The Allelopathic Effects of Two Species of Cistus Genus on Germination and Root Length of Ceratonia Siliqua L. - Omar, Mohamed A.; Masoud , Moussa; Albukhari, Abdulsalam A. (Al-Mukhtar Journal of Sciences, 2022)
This study examines the allelopathic effects of Cistus incanus (synonym C. villosus) L. and Cistus salviifolius L. on the germination and the root length of Ceratonia siliqua. Six aqueous extracts were prepared for both species by soaking fresh leaves in cold water, boiling leaves and leaving for 24 hours, and grinding dried leaves. The result suggests that the germination percentage was slightly affected by extract concentration regardless of the type of extraction since F-value and P-value at 0.05 confidence level were 2.93 and 0.043 respectively. However, root length showed a significant response to the type of extraction, extract concentration, and interaction between both factors as F-values reached 6.3, 12.4, and 2.4 respectively. LSD test showed the response of seeds germination was inverse with the increase of concentration. In addition, it showed that the extracts of dried leaves were higher in root inhibition than the extracts of fresh leaves. The interaction effect reached its highest values when comparing the dried leaves’ extract to the freshly soaked ones, even for the same concentrations. In conclusion, seeds of c. siliqua were able to easily start germination because the nutrition compounds needed were available in the endosperm, and the media supported them just by moisture for establishment. While for root length, the root tissue absorbed extra quantities of the inhibiting agents from media leading to failure or weakness in root development.